Identifying analogs of future thermal comfort under multiple projection scenarios in 352 Chinese cities. (July 2022) - Wang, Shasha; Zhan, Wenfeng; Du, Huilin; Wang, Chenguang; Li, Long; Jiang, Sida; Fu, Huyan; Miao, Shiqi; Huang, Fan
Highlights: Future UTCI analogs were determined in 352 cities for various scenarios and periods. The UTCI similarity decreases over time and with increasing emissions. The UTCI analog shifts in northern and southern cities significantly differ. The UTCI analog shifts are more intense compared with temperature analogs. Abstract: Thermal comfort analogs can be used to quantify the similarity of thermal comfort between current and future climates and are critical for raising awareness of future climate change. However, the similarity of thermal comfort analogs in consecutive future periods and under different emission scenarios remains unclear. This knowledge gap has significantly limited our understanding of future climate change and its effects on the living environment, especially from a human perception perspective. In this study, we identified the universal thermal climate index (UTCI) analogs of 352 cities in China under four specific emission scenarios for future periods (2021–2080). The results show that the UTCI analogs show significant spatial differentiation between cities. The analogs of northern cities primarily shift to cities with a neighboring latitude (–5° to 5°), whereas most central and southern cities mainly shift their analogs to lower-latitude cities. The shift to lower-latitude cities with latitude differences exceeding 5° is enhanced with time and increased anthropogenic emissions. In addition, compared with the temperature analogs, the shift of UTCI analogs is more intense and the shift direction is more complex. The results of this study provide insights into future climate change and heat-related health risks.